ETIKA LINGKUNGAN PADA KARYA DESAIN INTERIOR - Kusumowidagdo, Astrid (Institute of Research and Community Outreach - Petra Christian University, 2005)
The constant decrease in the external environmental condition has influenced the decline of the quality of life. It is thus an obligation to make improvement efforts to minimize the negative effects on humans and their environment. This paper will describe how interior design can be a part of our efforts to participate in the preservation and sanitization of the environment. Ecology-oriented interior design may be one of the important answers to give contributions to both the inhabitant and the global environment. In fact%2C the newly developed aesthetics today can be viewed from the adaptation of an interior design towards the surrounding environment. Some obstacles that may occur are also identified here originating from the human demand for efficiency%2C comfort%2C economic scale and even the aesthetic value. But all this is our responsibility as designers to participate in the implementation of sustainable design in order to improve the quality of life. Abstract in Bahasa Indonesia : Semakin menurunnya kondisi lingkungan luar%2C memberikan pengaruh pada menurunnya kualitas hidup. Untuk itu dirasa perlu adanya upaya perbaikan untuk meminimalisasi efek-efek negatif baik pada manusia maupun pada lingkungan. Tulisan ini akan memaparkan bagaimana karya desain interior dapat menjadi bagian dari upaya untuk turut serta dalam penyelamatan dan penyehatan lingkungan. Interior berorientasi ekologis dapat merupakan salah satu jawaban untuk dapat memberikan kontribusi baik bagi penghuni maupun lingkungan. Bahkan estetika dapat ditinjau dari adaptasi sebuah desain interior terhadap lingkungan sekitarnya. Beberapa hambatan yang mungkin terjadi%2C juga diidentifikasikan di sini%2C di mana ia berasal dari tuntutan manusia akan kemudahan%2C kenyamanan%2C skala ekonomis dan bahkan estetika. Namun semuanya ini merupakan kewajiban desainer untuk turut serta memikirkan sebuah desain yang berkelanjutan bagi peningkatan kualitas hidup masyarakat. environmental ethics%2C eco interior%2C ecological design.